Mental health in Peru after political violence. Itinerant interventions - Kendall, Rommy (2006)
Mental health has evolved as a main sanitary goal at national level because of the more participative, inclusive and equitable rostrum of current health politics. Political violence, present during the last twenty years in our country, has had high social, economical, moral and health costs. Today's impact is evidenced not only by the generation that lived the armed conflict, but also by the following generations. Feelings of distrust, fear and hopelessness are interlaced with the projects of development and generation of social capital in rural populations, decreasing their well-being and productivity. The international and national decision taken by the World Health Organization and the Peruvian Ministry of Health on the importance and intervention on mental health has generated actions addressed to enabling health workers of affected regions, as well as offering care and follow-up to people affected by the armed conflict. Results of our experience as the Peruvian Ministry of Health's National Institute of Mental Health itinerant technical team on three Peruvian departments and our ongoing intervention are described in this article.